2011
DOI: 10.1103/physrevstab.14.054001
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective optimization of dynamic aperture

Abstract: Dynamic aperture (DA) is one of the key nonlinear properties for a storage ring. Although there have been both analytical and numerical methods to find the aperture, the reverse problem of how to optimize it is still a challenging problem. A general and flexible way of optimizing the DA is highly demanded in accelerator design and operation. In this paper, we discuss the use of multiobjective optimization for DA. First we consider using objective functions based only on numerical tracking results. Data mining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…GAs were originally introduced to particle accelerator related research for a wiggler design in the early 1990s [6]. Thereafter, they have been successfully applied in more areas such as designing injector systems [7], diagnosing and designing accelerating cavities [8][9][10][11][12], and optimizing beam optics design in storage rings [13][14][15]. Some of these applications of GAs in the particle accelerator community are well summarized in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…GAs were originally introduced to particle accelerator related research for a wiggler design in the early 1990s [6]. Thereafter, they have been successfully applied in more areas such as designing injector systems [7], diagnosing and designing accelerating cavities [8][9][10][11][12], and optimizing beam optics design in storage rings [13][14][15]. Some of these applications of GAs in the particle accelerator community are well summarized in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[10]). However, if a more thorough search of the parameter space is desired in order to gain more assurance that the global minimum is reached, stochastic optimization algorithms such as genetic algorithms [4,5,11,12] and particle swarm optimization (PSO) algorithms [6,13,14] can be used. Studies have indicated the particle swarm method is a few times more efficient than a widely used genetic algorithm because solutions evaluated by the former are considerably more diverse than that of the latter.…”
Section: Considerations Of Online Optimization Of Nonlinear Beam mentioning
confidence: 99%
“…In recent years advanced multiobjective optimization methods have been widely used for the optimization of nonlinear beam dynamics in storage ring lattice design [4][5][6], which in simulation can significantly improve the dynamic and momentum apertures. However, given the potential differences between the real machine and the lattice model, it is likely that the optimal condition as determined by the model optimization will not give the expected result in the machine.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper an available framework of an evolutionary algorithm is applied that is complemented with a local search. Several papers such as [4][5][6][7][8][9][10] already showed the successful application of evolutionary algorithms like particle swarm, differential evolution or NSGA-II [11] in connection with particle accelerator modelling.…”
Section: Introductionmentioning
confidence: 99%